2021
DOI: 10.1136/svn-2021-001280
|View full text |Cite
|
Sign up to set email alerts
|

AHORA: a Spanish language tool to identify acute stroke symptoms

Abstract: ObjectiveTo develop a Spanish language tool for acute stroke identification.MethodsA Spanish language translation of the Balance-Eyes-Face-Arm-Speech-Time tool was developed within our emergency medical services agency.ResultsThe authors present a new prehospital stroke tool, Andar, Hablar, Ojos, Rostro and Ambos Brazos o Piernas (AHORA) (which means now in Spanish) to help combat the language barrier and reinforce the necessity to call 9-1-1 as soon as any stroke symptoms are noted.ConclusionAHORA is a Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It has been shown that educational tools for patients in English cannot be translated literally into Spanish and there are benefits of creating dedicated tools for Hispanic patients. 38 Therefore, reinforcing the similarity of VISIBL mnemonic in English and Spanish has the potential to increase the likelihood of MS awareness and symptoms recognition among US-born Spanish speakers and also Spanish speakers in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that educational tools for patients in English cannot be translated literally into Spanish and there are benefits of creating dedicated tools for Hispanic patients. 38 Therefore, reinforcing the similarity of VISIBL mnemonic in English and Spanish has the potential to increase the likelihood of MS awareness and symptoms recognition among US-born Spanish speakers and also Spanish speakers in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although the acronym translates to “now” in English, “ahora” alone does not emphasize urgency unless it is paired with the Spanish word “mismo,” because “ahora mismo” implies immediately or urgently. The word “ahora” on its own is more commonly used to mean “the present moment” or “in a minute.”10 Furthermore, additional text is necessary to indicate the need to activate emergency medical services quickly. The text associated with the acronym itself does not include the call to action.…”
mentioning
confidence: 99%
“…The word "ahora" on its own is more commonly used to mean "the present moment" or "in a minute." 10 Furthermore, additional text is necessary to indicate the need to activate emergency medical services quickly. The text associated with the acronym itself does not include the call to action.…”
mentioning
confidence: 99%
See 1 more Smart Citation